Comparative study between open (milligan morgan) haemorrhoidectomy and stapled haemorrhoidectomy - Bhagvat, Vikrant M.; Aher, Juily V.; Bhagvat, Shirish R. (International Surgery Journal, 2016)
Background:Haemorrhoids are one of the commonest afflictions of mankind from times immemorial. It is said that 40 percent of population have symptoms due to haemorrhoids at some time of their lives, a price possibly man has had to pay following the evolution of his erect posture. Conventional haemorrhoidectomy is a commonly performed operation for haemorrhoids, it has good results but is a painful procedure resulting in a hospital stay for variable days and time off work for two to six weeks. Stapled haemorrhoidectomy has come up as a new and promising procedure causing minimal post-operative pain, early discharge and quick return to work. Methods: In all 50 patients were included in the study - 25 underwent open and 25 underwent stapled haemorrhoidectomy. Computerised analysis of the data was done with the help of software computer programme MS Excel and Statistical 1984-1999. Significance levels were determined by using averages, standard deviation, unpaired student t test, Mann Whitney U test (for non-parametric skewed distribution) and Fischer exact test. If p value < 0.01 or < 0.001, the difference is highly significant. If p value < 0.05, the difference is significant Results:the stapled procedure for haemorrhoids is superior to Milligan Morgan haemorrhoidectomy in terms of post-operative pain, operative time and return to normal activities. It is straightforward and easy to learn. Early functional and symptomatic outcomes have been satisfactory and appear to be similar or better than those achieved using conventional technique. However, long term follow up with respect to these factors is necessary. Conclusions:Stappled haemorrhoidectomy is superior to open haemorrhoidectomy in terms of less intraoperative blood loss,less time for surgery,less pain in postoperative period, less stay in hospital,less post operative complications and early return to work.